Development of Archimedes Law Material E-Module on Motion Systems to Improve Student's Concept Understanding - Yanarti Yanarti; Jumadi Jumadi; Ira Lelita; Wiwin Rosiningtias (Postgraduate, University of Mataram, 2022)
The development research carried out intends to develop an Archimedes Law Material E-Module on the Motion System to improve the understanding of the Learner's Concept. Product development uses the ADDIE model. Validation of material experts, media experts and testing the responses of teachers and students is a product trial design carried out. The validation of the material and the E-module media was carried out by five peer reviewers, the teacher response questionnaire was carried out by four teachers from several schools in Yogyakarta and Central Java. The E-Modul trial was tested on 25 class VIII students of SMPIT Bakti Insani with a quasi-experimental pretest posttest control group design. The results of the material expert validation data showed an average of 96.67% in the